Estudo da toxicidade e potencial antitumoral do análogo da piperina 2-oxo-2-(4-etilfenilamina)-piperinoato de etila - Sousa, Tatyanna Kélvia Gomes de (2015)
Cancer is characterized by uncontrolled proliferation of abnormal cells. The high mortality rate associated with the disease, coupled to severe side effects caused by conventional treatments and the increasing development of resistance, has conducted to the demand for effective therapies with less toxicity. In this context, it is of great relevance the synthesis of synthetic products with structures based on natural products, which continue to be the main source of new medicines. In order to increase the effect and minimize the toxicity of piperine, an amide alkaloid with antitumor activity, it was obtained novel synthetic analogues, among them the 2-oxo-2-(4-ethylamine)-piperinoato acetate (HE-03). This study aimed to investigate the antitumor activity and toxicity of HE-03. The data demonstrate that HE-03 induced a small percentage of hemolysis to the highest concentration tested (1250 mg/mL), which suggests low toxicity to erythrocytes. In the preclinical acute toxicity study, the treatment with doses of 300 mg/kg and 2000 mg/kg of HE-03 in mice caused no deaths, and the changes observed in the CNS and ASN level were transient (30 min.). The LD50 value was estimated to be about 5000 mg/kg. HE-03 (6.25, 12.5 and 25 mg/kg) showed significant antitumor activity in vivo in ascites Ehrlich carcinoma model, especially considering the viability parameters and total cell. Its effect in doses of 12.5 and 25 mg/kg was similar to the one observed for the anticancer drug 5-fluorouracil (25 mg/kg). Cell cycle profile analysis showed that treatment with HE-03 (12.5 mg/kg) induced the appearance of sub-G1 peak, which was accompanied by a reduction in the number of cells in G0/G1 and S phases, suggesting induction of cell death by apoptosis. The treatment with HE-03 (12.5 mg/kg) significantly reduced peritumoral microvessels, which suggests anti-angiogenic activity. The toxicological analyzes indicate that the nine days of treatment with HE-03 at all doses, induced a significant increase in serum aspartate aminotransferase (AST) and urea. However, histopathology of the liver and kidneys showed that HE-03 does not induce changes of clinical importance. Leukopenia, accompanied by neutropenia, observed in animals treated with 25 mg/kg of HE-03 is one of the major side effects associated with cancer therapy. Futhermore, HE-03 did not induce an increase in the number of micronucleated erythrocytes in the micronucleus assay in peripheral blood, which indicates lack of genotoxicity in the evaluated conditions. Therefore, it is possible to infer that the synthetic analogue of studied piperine has potent antitumor activity in vivo, with mechanism that possibly involves the induction of apoptosis and antiangiogenic effects, as well as low toxicity.